The role of the Karelian-Finnish epic "Kalevala" in the ethno-cultural education of younger schoolchildren - Irina V. Komarova (Publishing house "Sreda", 2023)
The article deals with the issues of ethnocultural education of younger schoolchildren and the features of their solution in the modern information world; the results of an empirical study are presented, showing the insufficiently formed level of knowledge of the culture of the Karelian people by children on the example of the Kalevala epic, the development of which is mandatory in the educational space of the Republic of Karelia; examples of the use of the ideas of the synthesis of arts in the course of creating a choreographic work based on the Kalevala epic have been studied. The work is based on the author's observations of the process of studying the Karelian-Finnish epic "Kalevala" by students of primary school age in the conditions of the city of Petrozavodsk. The main research methods were theoretical analysis and experimental and practical work with an experimental group of younger schoolchildren. The author has studied the possibilities of applying the synthesis of arts in the formation of knowledge about the Kalevala epic. The epos "Kalevala" is included in the national-regional component of the educational program, the implementation of which makes it possible to achieve the tasks of ethno-cultural development and education of schoolchildren. However, in the conditions of multitasking pedagogical practice, forced to respond to all the challenges of the information world, the issues of preserving cultural traditions and transferring ethnocultural experience in the modern world become difficult to solve and depend on the stereotypes formed by modern mass media.